2019
DOI: 10.33394/j-lkf.v7i1.1906
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Scientific Approach toward Students' Critical Thinking Skills

Abstract: The role of education is to improve the quality of education, especially in producing high-quality students. High-quality students are those who are able to think critically, creatively, logically and take initiatives in responding to issues in society caused by the impact of the development of science and technology. This study aims to determine the effect of a scientific approach to students' critical thinking skills. This study is an experimental research with one group pretest-posttest design. The sample o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
(3 reference statements)
1
2
0
Order By: Relevance
“…The scheme showed that activities designed with a scientific approach could stimulate critical thinking skills. In line with the research (Triyani et al, 2019) shows that the use of scientific approaches affects the critical thinking ability of the child. How important it was to stimulate critical thinking skills in early childhood, considering the increasingly sophisticated world.…”
Section: Figure 2 the Relation Between Scientific Approach And Critical Thinking Aspectssupporting
confidence: 75%
“…The scheme showed that activities designed with a scientific approach could stimulate critical thinking skills. In line with the research (Triyani et al, 2019) shows that the use of scientific approaches affects the critical thinking ability of the child. How important it was to stimulate critical thinking skills in early childhood, considering the increasingly sophisticated world.…”
Section: Figure 2 the Relation Between Scientific Approach And Critical Thinking Aspectssupporting
confidence: 75%
“…The scientific learning process is considered one of the weapons or approaches used in learning in Indonesia today. This learning can encourage students to think critically, analytically, and logically in identifying a problem, understanding, solving problems from a case, and applying learning materials well [40]. Based on the gain score obtained from each aspect of students' critical thinking skills as measured through test result, it can be concluded that, six aspects of students' critical thinking skills can be improved through learning tools that are integrated with a scientific approach.…”
Section: Critical Thinking Skills Testmentioning
confidence: 99%
“…Research by Triyani, et.al. that there is an effect of using a scientific approach on students' critical thinking skills (Triyani, Herayanti, & Gummah, 2019). In addition, based on research Sani, scientific approach-based learning can emerge higher-order thinking skills (Sani, 2015).…”
Section: Point Of Viewmentioning
confidence: 99%